454 - Amendments to the Staff Rules Concerning the Annual Disclosure Statement and Leaves of Absence for Training - Executive Committee (EC) (2017)
(DT-487) Propuesta de Enmiendas al Reglamento de Personal y al Reglamento de la Dirección General